Performance of Concrete Reinforced With Recycled Tyre Steel Fibres at Elevated Temperatures (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Concrete is very low in ductility; to improve this property, the use of steel fibres spread in all its sections to reinforce it, has been studied by many researchers. Steel fibres are short metallic materials of small diameter, manufactured from steel ore, in the absence of adequate manufacturing steel factories in a third world country like Nigeria, the utilization of steel fibres derived from recycled waste tyre wire as reinforcement in concrete has been investigated in this study, focusing on its impact on the mechanical properties of concrete after exposure to elevated temperatures. Concrete specimens with varying fibre dosages (0%, 0.5%, 1%, and 1.5%) were evaluated for compressive, split tensile, and flexural strengths after 28days curing, at ambient temperature and high temperatures. Furthermore, concrete reinforced with steel fibres exhibited improved compressive strength retention after exposure to temperatures ranging from 200°C to 800°C compared to control concrete. However, there was no significant strength retention of split tensile strength at elevated temperatures. There was a direct correlation between flexural strength loss after elevated temperature exposure, and increase in fibre dosage. Microstructural analysis revealed differences in the morphology of concrete specimens before and after exposure to high temperatures. Overall, this study underscores the beneficial effects of incorporating recycled waste tyre wire as fibre reinforcement in concrete, offering a sustainable solution for enhancing the mechanical properties and resilience of concrete structures in both normal and high-temperature environments.